Method for testing competitive adsorption performance of porous carbon in high-humidity environment

By constructing an atomic-level model of porous carbon and performing GCMC simulations, combined with experimental verification, the problem of VOCs adsorption capacity reduction caused by competitive adsorption of water molecules under high humidity conditions was solved, the modification scheme of porous carbon was optimized, and efficient VOCs adsorption performance testing was achieved.

CN121703312APending Publication Date: 2026-03-20GUANGZHOU VOCATIONAL COLLEGE OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511988886.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

In high humidity environments, the VOCs adsorption capacity of porous carbon materials decreases due to competitive adsorption by water molecules. Traditional modification methods destroy the pore structure, and pure molecular simulation technology, without experimental verification, leads to insufficient predictive reliability.

Method used

An atomic-level model of porous carbon was constructed and verified by GCMC simulation combined with experiments. Modified porous carbon AC-MA was prepared, and its pore size and hydrophobicity were optimized. Fixed-bed adsorption tests were conducted and the performance was evaluated by mixing the modified porous carbon with myristic acid.

Benefits of technology

It improved the adsorption capacity of VOCs under high humidity conditions, shortened the screening cycle, improved the design efficiency of the modification scheme by 3 times, enhanced the adsorption energy of toluene, showed a significant hydrophobic effect, and had an adsorption capacity error of less than 5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121703312A_ABST
    Figure CN121703312A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing competitive adsorption performance of porous carbon in a high-humidity environment. The method comprises the following steps: performing quantitative characterization on AC to obtain physical parameters of the AC; preparing modified porous carbon; the method comprises the following steps: constructing an atomic-scale model based on physical parameters of AC and XPS functional group data of the AC, and generating structural stereoscopic models of the AC and AC-MA through Materials Studio software; performing GCMC simulation, calculating an adsorption isotherm, adsorption energy and a radial distribution function, and analyzing a radial distribution function curve to research the interaction among porous carbon atoms; an experiment verifies that the prepared AC-MA is subjected to a fixed bed adsorption test, a penetration curve is detected through GC, the simulated adsorption amount and the actually measured adsorption amount are compared, and a required error lt is obtained; 5%; and finally performing performance evaluation. According to the method, the screening period is shortened from 2 weeks to 5 hours, and the design efficiency of a modification scheme is improved by 3 times; the alkyl chain can improve the performance through hydrophobic effect and enhanced toluene adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous carbon materials technology, and more specifically, to a method for testing the competitive adsorption performance of porous carbon under high humidity conditions. Background Technology

[0002] Volatile organic compounds (VOCs) are defined by the World Health Organization as organic compounds with a saturated vapor pressure greater than 70 Pa at room temperature and a boiling point below 260 °C at normal pressure. They originate from various fields, including coal chemical industry, petrochemical industry, fuel and coating manufacturing, and solvent manufacturing and use. Due to their toxicity, irritancy, teratogenicity, and carcinogenicity, VOCs can cause serious harm to human health. Furthermore, VOCs are important precursors to haze and photochemical smog, and are among the major pollutants that harm the ecological environment. In recent years, a series of technologies have been explored and developed to separate and remove VOCs, among which adsorption technology is considered a highly efficient and economical strategy.

[0003] Current porous carbon materials exhibit significant limitations in treating volatile organic compounds (VOCs) under high humidity conditions (80% RH). Traditional porous carbon (such as unmodified activated carbon AC) readily forms hydrogen bonds with water molecules due to its hydrophilic functional groups (hydroxyl and carboxyl groups), leading to competitive adsorption of water vapor. This causes the toluene adsorption capacity to plummet from 472 mg / g under dry conditions to 151 mg / g at 80% RH. Existing modification techniques, such as polydimethylsiloxane (PDMS) coatings, can improve hydrophobicity, but they clog pores (reducing specific surface area by approximately 30%) and rely on expensive chemicals. While molecular simulation techniques (such as Chinese patent CN114456716A) are used for adsorption prediction, they lack experimental verification under high humidity conditions, resulting in insufficient predictive reliability. Therefore, we propose a method for testing the competitive adsorption performance of porous carbon under high humidity conditions. Summary of the Invention

[0004] To address the shortcomings of existing technologies, one of the objectives of this invention is to provide a method for testing the competitive adsorption performance of porous carbon under high humidity conditions, thereby solving the technical problem of reduced VOCs adsorption capacity due to competitive adsorption of water molecules under high humidity conditions.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for testing the competitive adsorption performance of porous carbon under high humidity conditions includes the following steps: (1) Quantitative characterization of unmodified porous carbon AC to obtain its physical parameters, including specific surface area and micropore volume; (2) Preparation of modified porous carbon: Unmodified porous carbon AC and myristic acid are mixed in a mass ratio and stirred at a constant temperature to obtain modified porous carbon AC-MA; (3) Model construction: Based on the physical parameters of unmodified porous carbon AC and its XPS functional group data, an atomic-level model was constructed, and structural three-dimensional models of modified porous carbon AC and modified porous carbon AC-MA were generated using Materials Studio software. (4) GCMC simulation: By calculating the adsorption isotherm, adsorption energy and radial distribution function, and by analyzing the radial distribution function curve, the interaction between porous carbon atoms is studied; (5) Experimental verification: The modified porous carbon AC-MA prepared in step (2) was subjected to fixed bed adsorption test. The breakthrough curve was detected by GC, and the simulated and measured adsorption amounts were compared. The error was required to be <5%. (6) Performance evaluation: Calculate the adsorption selectivity using the following formula:

[0006] If S ads >100 and E ads <-0.5eV, it is judged to be a highly efficient adsorbent.

[0007] This invention addresses the problems of decreased VOCs adsorption capacity due to competitive adsorption of water molecules under high humidity, damage to pore structure caused by traditional modification methods, and lack of coupling of pure molecular simulation technology with experimental verification by constructing an atomic-level model of porous carbon and conducting GCMC simulation. It combines experimental verification and performance evaluation. The invention has advantages such as small error between simulated and experimental adsorption capacity (e.g., AC-MA toluene adsorption simulation value of 1.28 g / g, measured value of 1.16 g / g), short screening cycle (shortened from 2 weeks to 5 hours), and a 3-fold increase in the efficiency of modification scheme design, revealing that alkyl chains improve performance through hydrophobic effects (contact angle >130°) and enhanced toluene adsorption energy (-0.90 eV).

[0008] Preferably, in step (1), the specific surface area of ​​the unmodified porous carbon AC is ≥1500 m². 2 / g, micropore volume ≥0.8cm³ 3 / g.

[0009] Preferably, in step (2), the mass ratio of the unmodified porous carbon AC to myristic acid is 0.52:1.

[0010] Preferably, in step (2), the temperature of the constant temperature stirring is 65°C, the stirring time is 18h, and the stirring speed is 300rpm.

[0011] Preferably, in step (2), the modified porous carbon AC-MA obtained has a pore size distribution of 0.5-3.5 nm and a density of 1.8-2.1 g / cm³. 3 .

[0012] Preferably, in step (3), the XPS functional group data of the modified porous carbon AC are CC peak 284.4 eV and OC=O peak 288.5 eV.

[0013] Preferably, in step (4), the GCMC simulation parameters are set to a temperature of 298K, a pressure of 0-20kPa, a COMPASS force field, and a cutoff radius of 1.55nm.

[0014] Preferably, in step (4), the formula for adsorption energy is Eads = ETotal - EAC - EGas.

[0015] Preferably, in step (4), the test conditions for the fixed bed adsorption test are 80%RH, toluene concentration of 100ppm, and flow rate of 100mL / min.

[0016] Compared with the prior art, the beneficial effects of the present invention are: This invention addresses the problems of decreased VOCs adsorption capacity due to competitive adsorption of water molecules under high humidity, damage to pore structure caused by traditional modification methods, and lack of coupling of pure molecular simulation technology with experimental verification by constructing an atomic-level model of porous carbon and conducting GCMC simulation. It combines experimental verification and performance evaluation. The invention has advantages such as small error between simulated and experimental adsorption capacity (e.g., AC-MA toluene adsorption simulation value of 1.28 g / g, measured value of 1.16 g / g), short screening cycle (shortened from 2 weeks to 5 hours), and a 3-fold increase in the efficiency of modification scheme design, revealing that alkyl chains improve performance through hydrophobic effects (contact angle >130°) and enhanced toluene adsorption energy (-0.90 eV). Attached Figure Description

[0017] Figure 1 This is a three-dimensional model of the optimized porous carbon (AC-MA) structure in this invention; Figure 2 This is a three-dimensional model of the unmodified porous carbon (AC) structure in this invention; Figure 3 The images show the adsorption isotherms of water (a) and toluene (b) in the AC and AC-MA structural models in the embodiments of the present invention. Figure 4 The diagram shows the radial distribution function (RDF) curves between porous carbon atoms in the AC and AC-MA structural models in the embodiments of the present invention. Figure 5 The figures show the dynamic adsorption curves (a, b), adsorption amount (c), and adsorption amount change curve (d) of AC and AC-MA under different humidity conditions in the embodiments of the present invention. Figure 6 The diagram shows the most stable adsorption configurations of water and toluene molecules on the AC (a and b) and AC-MA (c and d) surfaces in the embodiments of the present invention, and their adsorption energies. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available. For any specific techniques or conditions not specified in the examples, they can be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions.

[0020] This embodiment provides a method for testing the competitive adsorption performance of porous carbon under high humidity conditions. It addresses the problem of VOCs adsorption decreasing by more than 50% due to water molecule competitive adsorption under high humidity conditions by integrating molecular simulation and experimental verification. The specific steps are as follows: 1. Model Building (1) Based on the physical parameters of porous carbon (specific surface area ≥1500m2 / g, micropore volume ≥0.8cm3 / g) and XPS functional group data (CC peak 284.4eV, OC=O peak 288.5eV), an atomic-level model was constructed.

[0021] (2) Optimize pore size distribution (0.5-3.5 nm) and density (1.8-2.1 ≥ 0.8 cm3 / g), and generate AC (unmodified) and AC-MA (alkyl-modified) models using MaterialsStudio software, such as Figure 1 , Figure 2 As shown ( Figure 1 The basic structural unit (BSU) of porous carbon and the three-dimensional model of porous carbon structure AC(a) are given. Figure 2 The optimized porous carbon structure stereo model and AC-MA(b) are shown.

[0022] 2. GCMC Simulation (1) Setting parameters: temperature 298K, pressure 0-20kPa, COMPASS force field, cutoff radius 1.55nm.

[0023] (2) Calculate the adsorption isotherm (e.g.) Figure 3 As shown, Figure 3 The adsorption isotherms of water (a) and toluene (b) in the AC and AC-MA structural models, adsorption energies (formula: Eads = ETotal - EAC - EGas), and radial distribution functions (e.g.) Figure 4 As shown, Figure 4(Radial distribution function (RDF) curves between porous carbon atoms in AC and AC-MA structural models).

[0024] 3. Experimental verification (1) Preparation of modified porous carbon (AC-MA): Unmodified porous carbon AC and myristic acid were mixed at a mass ratio of 0.52:1 and stirred at 65°C for 18 h at a stirring rate of 300 rpm.

[0025] (2) Fixed-bed adsorption test: 80% RH, toluene concentration 100 ppm, flow rate 100 mL / min, GC detection breakthrough curve (e.g. Figure 5 As shown, Figure 5 The dynamic adsorption curves (a, b), adsorption amount (c), and adsorption amount change curve (d) of AC and AC-MA under different humidity conditions are shown, and the simulated and measured adsorption amounts are compared (error <5%).

[0026] 4. Performance Evaluation The adsorption selectivity is calculated using the following formula:

[0027] If S ads >100 and E ads <-0.5eV, it is judged to be a highly efficient adsorbent.

[0028] This invention addresses the problems of decreased VOCs adsorption capacity due to water molecule competitive adsorption under high humidity conditions, damage to pore structure caused by traditional modification methods, and lack of coupling of pure molecular simulation technology with experimental verification by constructing an atomic-level model of porous carbon and conducting GCMC simulations. Combined with experimental verification and performance evaluation, it solves these problems. The invention features small errors between simulated and experimental adsorption capacities (e.g., AC-MA toluene adsorption simulated value 1.28 g / g, measured 1.16 g / g), reduces the screening cycle from 2 weeks to 5 hours, and improves the design efficiency of modification schemes by 3 times. Figure 6 As shown, the alkyl chain enhances the performance through hydrophobic effects (contact angle >130°) and enhanced toluene adsorption energy (-0.90 eV).

[0029] The embodiments disclosed in this invention are preferred embodiments, but are not limited thereto. Those skilled in the art can easily understand the spirit of this invention based on the above embodiments and make different extensions and variations, but as long as they do not depart from the spirit of this invention, they are all within the protection scope of this invention.

Claims

1. A method for testing the competitive adsorption performance of porous carbon under high humidity conditions, characterized in that, Includes the following steps: (1) Quantitative characterization of unmodified porous carbon AC to obtain its physical parameters, including specific surface area and micropore volume; (2) Preparation of modified porous carbon: Unmodified porous carbon AC and myristic acid are mixed in a mass ratio and stirred at a constant temperature to obtain modified porous carbon AC-MA; (3) Model construction: Based on the physical parameters of unmodified porous carbon AC and its XPS functional group data, an atomic-level model was constructed, and the structural three-dimensional models of modified porous carbon AC and modified porous carbon AC-MA were generated by Materials Studio software. (4) GCMC simulation: By calculating the adsorption isotherm, adsorption energy and radial distribution function, and by analyzing the radial distribution function curve, the interaction between porous carbon atoms is studied; (5) Experimental verification: The modified porous carbon AC-MA prepared in step (2) was subjected to fixed bed adsorption test. The breakthrough curve was detected by GC, and the simulated and measured adsorption amounts were compared. The error was required to be <5%. (6) Performance evaluation: Calculate the adsorption selectivity using the following formula: ; If S ads >100 and E ads <-0.5eV, it is judged to be a highly efficient adsorbent.

2. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (1), the specific surface area of ​​the unmodified porous carbon AC is ≥1500 m². 2 / g, micropore volume ≥0.8cm³ 3 / g.

3. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (2), the mass ratio of the unmodified porous carbon AC to myristic acid is 0.52:

1.

4. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that, In step (2), the constant temperature stirring temperature is 65℃, the stirring time is 18h, and the stirring speed is 300rpm.

5. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (2), the modified porous carbon AC-MA obtained has a pore size distribution of 0.5-3.5 nm and a density of 1.8-2.1 g / cm³. 3 .

6. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (3), the XPS functional group data of the modified porous carbon AC are CC peak 284.4 eV and OC=O peak 288.5 eV.

7. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (4), the GCMC simulation parameters are set to a temperature of 298K, a pressure of 0-20kPa, a COMPASS force field, and a cutoff radius of 1.55nm.

8. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (4), the formula for adsorption energy is Eads = ETotal - EAC - EGas.

9. The method for testing the competitive adsorption performance of porous carbon under high humidity conditions according to claim 1, characterized in that: In step (4), the test conditions for the fixed bed adsorption test are 80%RH, toluene concentration of 100ppm, and flow rate of 100mL / min.

Citation Information

Patent Citations

  • Alumina polishing solution for polishing sapphire and preparation method thereof

    CN114456716A